[PP.12.16] VALSARTAN TREATMENT IMPROVED RETINAL CAPILLARY RAREFACTION IN HYPERTENSIVE PATIENTS. (September 2016) - Jumar, A.; Harazny, J.M.; Ott, C.; Kistner, I.; Friedrich, S.; Schmieder, R.E.
Abstract : Objective: Decreased capillary density influences vascular resistance, perfusion and metabolism. In animal studies and clinical trials investigating skin capillaries of hypertensive patients, antihypertensive treatment decreased capillary rarefaction. In face of the evidence that retinal vessels may mirror cerebral microcirculation, the aim of this study is to investigate the influence of the renin-angiotensin-receptor-blocker valsartan on retinal capillary rarefaction in patients with hypertension. Design and method: This is a comparative study consisting of 55 healthy male and female individuals and 95 male and female patients with hypertension stage 1 or 2, who participated in clinical trials during 2007 and 2015 at the Clinical Research Department, University Erlangen. Hypertensive patients received standardized open-label treatment with valsartan for 4 weeks after 4 weeks wash-out period of previous antihypertensive medication. Retinal vascular parameters were measured non-invasively and in vivo by scanning laser Doppler flowmetry (Heidelberg Engineering, Germany) before and after treatment with valsartan in the hypertensive group and compared to a healthy control population. Retinal capillary rarefaction was determined with the parameters intercapillary distance (ICD) and capillary area (CapA). Results: In the hypertensive group (age 54 ± 11 years) there was a decrease in systolic and diastolic office and 24-hour ambulatory blood pressure (BP) (all p < 0.001) after 4 weeks therapy with valsartan. ICD decreased after treatment with valsartan (23.4 ± 5.5 μm vs 21.5 ± 5.6 μm, p < 0.001) and CapA increased after 4 weeks treatment with valsartan (1564 ± 621 vs 1776 ± 795, p = 0.001) compared to baseline. Compared to the healthy normotensive control group, (age 53 ± 13 years, ICD 20.2 ± 4.2 μm, CapA 1821 ± 652), untreated hypertensive patients showed greater ICD (p < 0.001) and smaller CapA (p = 0.019), whereas treated hypertensive patients showed no difference in ICD (p = 0.126) and CapA (p = 0.728). Conclusions: Antihypertensive therapy with valsartan for four weeks diminished capillary rarefaction in patients with hypertension stage 1 or 2.